We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#1**0 **

I believe this is how you do it.

Use the formula to factor: a^2+b^2=(a+b)(a-b)

y^2 is already a perfect square.

49=7*7=7^2 and that's your other perfect square.

Now your expression is y^2+7^2=(y-7)(y+7)

RainbowPanda Sep 12, 2018

#3**+1 **

That's not quite right RP! The general expression is a^{2} - b^{2} = (a + b)(a - b)

Here we have a = y, but b = 7i, where i is the square root of -1.

So y^{2} + 49 → y^{2} - (7i)^{2} → (y + 7i)(y - 7i) (Note that i^{2} = -1)

Alan
Sep 12, 2018

#4**0 **

Figures, I knew the actual equation but I thought that was only for - and not +. Thanks for correcting me though!

RainbowPanda
Sep 12, 2018